Valuasi Ekonomi Pemandian Bah Tio Sampuran - Romario F D Purba; Rizky Sahertian; Pawer D Panjaitan; Rafael E J Siregar; Muhammad Fauzi; Ahmad Tarez Azhadi (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This research was conducted Bah Tio Sampuran baths at Simalungun Regency in May 2025. The research objective was to analyze the economic value of natural resources of Bah Tio Sampuran bathing place. This research used survey method. Data were collected by direct observation and interviews with respondents to identify and classify patterns of natural resource utilization and to determine the value of natural resources as measured by the community's willingness to pay or accept an environmental change. Data analysis used economic valuation techniques to calculate the total economic value (TEV) of the natural resources.